Highly Sensitive Spectrofluorimetric Determination of Doxycycline Using Doxycycline-Europiumion-Sodium Dodecyl Sulfonate System - Jia, Baoxiu; Zhang, Ping; Wang, Renliang; Li, Yuqin; Liu, Caihong; Li, Li (Asian Journal of Chemistry, 2013)
A new sepctrofluorimetric method for the determination of doxycycline was developed based on its enhancement of the fluorescence intensity of europium ion in the presence of sodium dodecyl sulfonate. The mechanism of fluorescence enhancement was studied. Optimum conditions for the determination of doxycycline were also investigated. The linear range was 0.10-3.00 μg/mL. The detection limit was 1.3 ng/mL. There was no interference from the excipients normally used in tablet formulations and the serum compositions. The proposed method was successfully applied to the determination of doxycycline in tablets and serum.